Analisis Kesulitan Menulis Paragraf Deskripsi pada Siswa Kelas IV SD Negeri Jurug Bantul Yogyakarta - Azizah, Delila Rizki; Anafiah , Siti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sarjanawiyata Tamansiswa, 2024)
The aim of this research was to determine the difficulty of writing descriptive paragraphs for fourth grade students at Jurug Bantul Elementary School, Yogyakarta. This research is descriptive qualitative in nature. The results of the research show that: (1) The forms of difficulty in writing descriptive paragraphs among students are difficulty expressing ideas in sentence form, difficulty using the right vocabulary, inability to make paragraphs, difficulty using correct capital letters and punctuation, some students are not yet able to write neatly. (2) The causes of difficulty in writing descriptive paragraphs among students are the different abilities of each student. Low interest in writing among some studens, the age of students who are relatively low, limited mastery of vocabulary, the condition of some students during learing is not optimal, basic writing skills are not optimal. due to low levels of online learning in classes, the lack of parental role in the student learning process at home. (3) Efforts to overcome difficulties in writing descriptive paragraphs through a series of explanations and exercises regarding writing descriptive paragraphs, checking student writing, literacy, looking for new vovabulary and learning outside the classroom.